Balancing numbers which are concatenations of three repdigits - Erduvan, F.; Keskin, R. (Carpathian Mathematical Publications, 2024)
In this study, it is shown that the only balancing numbers which are concatenations of three repdigits are $204$ and $1189$. The proof depends on lower bounds for linear forms and some tools from Diophantine approximation.